The Use of LCD Projectors as Learning Media in Enhancing Students’ Interest in Learning Arabic at MAS NW Sepit - Siti Laila Rodia; Pebi Pebrianti; Siti Zihani; Nurul Hidayah; Siroja Muniro; Siti Rohima Badrudin; Nursaulatunnisa; Selsi Apriliani (Formad English Foundation NTB Jakarta, 2026)
This study examines the use of LCD projectors as instructional media and their influence on students’ interest in learning Arabic at MAS NW Sepit. The research is motivated by the persistent issue of low student interest in Arabic language learning, often resulting from monotonous, teacher-centered instructional practices and limited integration of instructional technology. In response to the growing demand for more interactive and student-centered learning in the digital era, this study aims to explore how LCD projectors are utilized in Arabic language instruction and to what extent their use enhances students’ learning interest. A qualitative descriptive approach was employed. Data were collected through classroom observations, interviews with Arabic language teachers, and documentation of teaching activities involving LCD projector use. The data were analyzed using data reduction, data display, and conclusion drawing techniques to identify patterns related to media utilization and student responses. The findings reveal that LCD projectors are systematically used to present Arabic learning materials in visual formats, including texts, vocabulary, images, and structured explanations. This visual presentation contributes to a more engaging learning environment by increasing students’ attention, reducing boredom, and encouraging active participation during lessons. Students demonstrated greater enthusiasm and focus when learning activities incorporated visual media compared to conventional instructional methods. In conclusion, the study indicates that LCD projectors function as effective instructional media that support students’ interest in learning Arabic. Integrating technology-based media into Arabic language instruction can enhance learner engagement and improve the overall quality of the learning process.